Results Comparison for Hat-shaped, Double-notch and Punch Testing of Split Hopkinson Shear Bar Technique - Bagus Budiwantoro; Iffah Faizah; Dini A. Prabowo; Burhan Febrinawarta; Muhammad Agus Kariem (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
The split Hopkinson shear bar (SHSB) test is a modification of the high rate-impact test using a split Hopkinson pressure bar (SHPB). The SHSB has been developed for a variety of techniques, for example, the hat-shaped (circular or flat), double-notch, and punch (with or without notch) techniques. The main purpose of this study was to compare these three techniques to determine the shear stress-shear strain of aluminum alloy 2024-T351. The study was conducted using the Abaqus/CAE® software. The circular hat-shaped and punch (with and without notch) techniques used a quarter-section solid 3D model. The flat hat-shaped and double-notch techniques used a half-section solid 3D model. This study successfully tested and compared the three SHSB techniques, with a number of considerations, i.e. the same parameter values for kinetic energy, shear area and shear angle. Each technique has its own advantages and disadvantages in terms of force equilibrium, flow stress fluctuation, constant strain rate, machine-ability, ease of experiment, etc. The optimum technique among the three is the hat-shaped technique.